Penerapan Flipbook Berbasis CIRC untuk Keterampilan Menulis Surat Pribadi dan Penilaian Sikap Komunikasi Kelas V - Rochima, Chandra Agustin; Purwati, Panca Dewi (YASIN, 2025)
Although cooperative learning models and digital media have been widely examined in the context of literacy instruction, studies that specifically integrate a flipbook based on the Cooperative Integrated Reading and Composition (CIRC) model to enhance personal letter writing skills and communication attitudes among elementary school students remain limited. This study aimed to describe the implementation of a CIRC-based flipbook, assess its effectiveness in improving personal letter writing skills, and analyze students’ communication attitudes during instruction. Employing a mixed-methods approach with a sequential explanatory design, the research involved 27 fifth-grade students selected through total sampling. Data were obtained through writing tests, observations, interviews, and documentation, and were analyzed using descriptive statistics and thematic analysis. The results show that 81% of students surpassed the KKTP benchmark, indicating that the CIRC-based flipbook is effective in improving personal letter writing skills. Qualitative data confirm that students displayed positive communication attitudes, particularly in terms of respect, responsibility, fairness, and caring. These findings reinforce cooperative learning theory and the use of interactive digital media in language instruction, and they underscore that collaborative digital media can support the enhancement of writing skills and the development of students’ communication attitudes. Follow-up studies are recommended to adapt similar models to other language skills and broader instructional contexts.